Protagonismo sociopolítico e religioso: uma análise do Movimento dos Focolares na cidade do Recife através da "teoria da ação comunicativa" de Jürgen Habermas - Claudino, Francisca Iolani Fernandes (2007)
This Work discusses persons-who are bonded to the Focolari Movement - social practices (sociopolitical and religious protagonism), based - this work debate - in Jürgen Habermas “Communicative Reason” i. e. Jurgen Habermas’ conception through his “discourse Ethics”. In modern society, “Instrumental, Reason” in its exarcebated sense, typical to Capitalism, conveys, as a kind, a sort of channel, man actions toward determined upshots, so to say inescapable purposes. Human rapports tend, are conducted to degradation, to take profit from everything and everyone, to bargain; they are rapports that are analogous, in all senses, to purchase and selling. In deeper instances, love vulgar interpretation is confounded with egoism, mixes with selfishness with each one in seeks to gain greedly always to detriment to the noblest feelings that are supposed to be, at any cost, suppressed. Nevertheless, “The Theory of Communicative Action” aims at understanding, through language, having as parameter “Consensus” which the actors behave in at liberty. Language coordinates men actions: it pretends having, aims at having an emancipating function. One is dealing with an approach directed to human identity construction, building several aspects, in a social rapport which, i.e. the abovementioned approach, based, founded in the Focolari Movement, departing from Discourse Analysis about the gathered material through interviews rendered, made possible, workable a certain parallel, comparison between the life proposals that the Focolari Movement persons adopted as their life goal, their utmost life purpose, their “Art of Love” liveliness, as well as they embraced Universal Fraternity and unity in diversity ideals, between, so to say, all these conceptions and deeds and the “Communicative Action Theory” presuppositions, so to say: best argument practice is dialogue. It was, also, possible to observe, to verify that both these conceptions constitutive elements are intercomplementary, compatible in their nature, being both these of them, nearly, each other foundation. At least, as one understands Jürgen Habermas`s theory, on can the Focolari Movement`s ideas, so to say Ideal. This research’s nucleus is found in the values recognition that bestows a great sense, meaning to actions, deeds that bring forth to this studied group protagonism.